Dynamic Modeling and Analysis of Electrodynamic Multi-tether System - Xialin Li; Keying Yang; Lincheng Li; Fuzhen Yao (Space: Science & Technology, 2023)
Electrodynamic tether (EDT) is a key prospective technique for space-debris removal without the use of propellant. However, there are 2 main shortcomings of the classical EDT system. One is that the conductive tether with a single wire should exceed several kilometers to produce the expected force, which increases the risk of collision and damage. The other is the heavy current or high voltage caused by the overlong tether, which may even melt itself. Therefore, a novel electrodynamic multi-tether (EMT) system has been proposed here to overcome the above disadvantages of the classical EDT system. The EMT system has multi tethers connecting the 2 end bodies, which has more complex dynamic behaviors than the EDT system. In order to promote the application of the EMT system, this paper will pay attention to the dynamic modeling and analysis of the EMT system, to reveal the primary dynamic characteristics. Firstly, the dynamic equation of the novel EMT system was established. Secondly, the linear assumption and vibration theory were utilized to illustrate its primary dynamic characteristic. Finally, the expressions of the vibration period and critical current of tether were given and numerical simulations were conducted to verify these analyses. The results showed that the tether libration equation can be simplified when the size of main satellite is much smaller than that of tether. Besides, the tether will go tumbling immediately when the practical current exceeds the critical current.